2018
DOI: 10.1371/journal.pone.0200816
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic drug use and HIV infection among men who have sex with men in China: A sixteen-city, cross-sectional survey

Abstract: IntroductionIncreasing evidence suggests an association between synthetic drug use and HIV infection among men who have sex with men (MSM). The aim of this study was to evaluate synthetic drug use prevalence, describe characteristics of synthetic drug users, and investigate whether synthetic drug use is associated with HIV infection among Chinese MSM.MethodsA cross-sectional survey was conducted in 16 Chinese cities among males >18 years old who reported having had sex with men in the prior 3 months, but did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…This decision was based on previous findings in China that recreational drug use amongst MSM remains high, while participation in group-sex remains low. [19,20] Though this imputation may lead to bias, this bias is assumed to be minor. [21]…”
Section: Methodsmentioning
confidence: 99%
“…This decision was based on previous findings in China that recreational drug use amongst MSM remains high, while participation in group-sex remains low. [19,20] Though this imputation may lead to bias, this bias is assumed to be minor. [21]…”
Section: Methodsmentioning
confidence: 99%
“…48 The Asian MSM populations studied include those living in the United States, 22 Japan, 26 Malaysia, 32 and major cities in Mainland China. [23][24][25][27][28][29][30][31][33][34][35][36][37][38][39][40][41][42][43][44][45][46]48 Both the general MSM population and sex workers at night clubs (money boys) have been studied. Data the use of recreational drugs in their lifetime, of which 21.3% used inhaled nitrites, 2.4% used crystal meth, and 1.0% used ecstasy.…”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…41 In a recent nationwide study in China involving 16 cities (n = 3135), 96.3% of the MSM who used synthetic tried inhaled nitrites in their lifetime. 45 Inhaled nitrites were also the most common recreational substance used among money boys in Changsha, a highly developed entertainment city in China, whereby 36.6% of the substance users reported ever use in the last 3 months of the survey. 36 Researchers suggested that the low cost of inhaled nitrites and high accessibility through online market and adult stores contributed to the prevalent use of inhaled nitrites in China.…”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…Recent studies revealed that recreational drugs were increasingly popular among MSM in China [ 3 5 ]. Recreational drug use was reported to be associated with risky sexual behaviors, which placed users at elevated risk of HIV and STDs [ 5 – 7 ].…”
Section: Introductionmentioning
confidence: 99%